New Orleans' Remarkably (Un)Predictable Recovery: Developing a Theory of Urban Resilience. (September 2015) - Hobor, George
In this article, I use New Orleans' experiences pre- and post-Katrina, as well as information on other cities exposed to shocks, to develop and advance an original explanation for urban resiliency. The explanation suggests that economic origins influence elite commitment to and participation within cities, thereby influencing the city's ability to redefine itself after experiencing an exogenous shock, whether it be a natural disaster, economic crisis, or any other threat. I show that New Orleans' economic origins were incompatible with the production of an elite that showed place commitment, which was needed for leadership and resources to recreate the city after Katrina. New Orleans' development mirrors that of other cities that have proven not to be durable. As a result, the city "came back" from Katrina as a smaller and more socially challenged version of its old self—a city still split by racial inequality. Thus, despite its climb out of the damage caused by Hurricane Katrina and the levee failures, New Orleans is not resilient. I conclude by reiterating the importance of leadership in building resiliency, especially in a place that is more likely than most others to experience a disaster.